Development of Sustainable Alkali-Activated Mortars Using Fe-Rich Fayalitic Slag as the Sole Solid Precursor - Adediran, Adeolu; Yliniemi, Juho; Illikainen, Mirja (Frontiers in Built Environment, 2021)
Vast amounts of water-cooled non-ferrous metallurgy slags are generated yearly, and significant amounts are unutilized or dumped in landfills. To address this issue, in this study, MgO-FeOx-SiO2 fayalitic slag (FS) was used as the sole solid precursor (as an aggregate and binder) in alkali-activated mortars. The performance of the mortar samples was analyzed in terms of workability, density, compressive strength, and ultrasonic pulse velocity. The microstructural properties and binder composition of the samples were studied using a scanning electron microscope (SEM) coupled with energy dispersive X-ray spectroscopy (EDS). Experimental results revealed that mortar samples made with FS aggregates performed better, achieving a 28-day compressive strength of 21 MPa compared to mortars produced with standard sand aggregates, which gained compressive strengths of 9 MPa. Further optimization of the particle size distribution of FS aggregate-based mortar samples using particle packing technology improved the workability, densified the mortar and yielded a mechanical performance of up to 40 MPa. FS aggregates have better interfacial bonding with the binder gel compared to standard sand, and the FS aggregates participate in the hardening reactions, consequently affecting the final binder phase composition, which consists of a Na2O-Fe2O3-SiO2 gel with lower quantities of CaO, MgO, and Al2O3. Therefore, the alkali-activated mortars produced based on the optimization of fully recycled industrial residues can provide a pathway for the sole utilization of metallurgical by-products, which can have a wide range of structural applications.